Long-term diverse rotation alters nitrogen cycling bacterial groups and nitrous oxide emissions after nitrogen fertilization. (October 2020) - Linton, Nicola F.; Ferrari Machado, Pedro Vitor; Deen, Bill; Wagner-Riddle, Claudia; Dunfield, Kari E.
Abstract: Agriculture accounts for a majority of global soil nitrous oxide (N2 O) emissions. Increased crop diversity can change soil nitrogen (N), physicochemical properties and alter belowground microbial communities, leading to changes in potential N2 O emissions when inorganic N fertilizer is applied. Nitrification and denitrification are two main N cycling pathways under investigation due to their contribution to soil N cycling and production of N2 O. The goal of this study was to understand the impacts of 35 years of crop diversification in shaping diversity and the community size and activity of nitrifier and denitrifier bacteria and N2 O emissions after N fertilization in corn. In 2017, after fertilizer addition, N2 O emissions were continuously measured using automatic chambers from a long-term experiment of simple (corn-corn-soybean-soybean) and diverse (corn-corn-soybean-wheat underseeded with red clover cover crop) four year rotations under second year corn. Soil was collected during peak N2 O emissions using high frequency temporal sampling to capture shifts in 16S rRNA, amoA, nirS, nirK, nosZ1 and nosZ2 genes and gene transcripts in soil where urea-ammonium-nitrate (UAN) was applied. An N2 O emission event occurred in both rotations following UAN application but was higher in the diverse rotation, which also had persistent higher total and denitrifying ( nirK and nosZ2 ) bacterial abundance. Bacterial amoA significantly increased in both rotations shortly after UAN addition, but gene detection decreased significantly in the simple rotation and remained elevated in the diverse. Transcripts for atypical nosZ2 were consistently detected but higher after UAN addition. Total bacterial diversity did not differ between simple and diverse rotations, however, abundance of microbial pathways leading to soil N2 O emissions, ammonia oxidizers and denitrifiers, were elevated in soil with a more diverse cropping history. Best management practices (BMPs) that include crop diversification need to consider microbial communities and greenhouse gas (GHG) production, in order to fully quantify the soil ecosystem services. Graphical abstract: Image 1 Highlights: Diversifying corn-soybean rotation with wheat and cover crops increased N2 O emissions. Nitrifying bacteria increased in response to inorganic N fertilizer application. Ammonia oxidizer gene abundance was positively correlated with N2 O emissions. Clade 2 N2 O-reductase-bearing denitrifiers were more abundant and active than Clade 1. Diversified corn rotations had greater soil moisture in the early growing season.